Development of an enzymatic method to quantify methyl ketones from bacterial origin - Fadda, Silvina G. (2002)
Methyl ketones are detected in dry fermented sausages in which they contribute to the cured aroma. They have been associated with the inoculation of Staphylococcus carnosus used as starter culture. To evaluate the ability of bacterial starters to produce methyl ketones it was necessary to develop a rapid method. The method consists of a reaction catalyzed by a commercial NADPH-dependent alcohol dehydrogenase that reduces the 2-pentanone to its secondary alcohol. The linearity, the specificity, and the robustness were studied. Its accuracy was confirmed by comparison with the gas chromatography technique. Finally, the method was validated on biological samples such as the 2-pentanone produced by Staphylococcus camosus. The enzymatic method offers some advantages over the gas chromatography, as it is faster, simpler, and inexpensive; guaranteeing an effective way to assess bacterial ketone production.